O processo de implementação e implantação dos CRAS em municípios da região oeste do estado do Paraná - Fidelis, Solange Silva dos Santos (2009)
This research aimed to understand how it has developed the process of implementation and deployment of CRAS in western Parana, considering the political administrative division of the State, the SETP by the Regional Office of Cascavel. First constructed a table with the profile of the municipalities that make up the coverage area of the ER in Cascavel, and from the data listed was established methodological procedures with clipping by intentional sampling by setting 7 of a total of 34 municipalities. It involved 10 professionals working in CRAS, 4 professionals in the management of municipal social care policy and 1 professional as the representative of the State Authorities in the region. In the data collection technique was used semi-structured interview in order to enable the construction of the profile of CRAS: conditions of physical infrastructure and human; the actions taken and the conditions that have been carried; conception of persons involved directly with the public social care as the SUAS and the CRAS; the relationship of CRAS and social care network in this context, considering also the conditions for the development of social care policy. It was then possible to view the progress made after initiating the deployment of SUAS, the limitations in that process and the challenges to the achievement of the advocates that the National Policy for Social Care/SUAS. It was possible from direct contact with the subjects, systematize and is currently regarded as the SUAS towns in the region, considering the different realities set in PNAS/SUAS at the rate of population municipalities, large and small porte I, and level of full and basic management. Considering the variety of realities and different degrees of development of social care policy, the research presented common issues, among which stands out: the lack of full team of human resources, physical structure and equipment inadequate; the vulnerable identity of CRAS, an issue exacerbated as installed in the same structure as previously established services, absence of social diagnosis to support interventions; wide emergency demand assuming seconded volume of actions taken hindering the advancement of social-educational work, and allocations of CRAS finally settled, especially as regards the relationship with the social care network in the territory. Finally, this work contributes to trigger the debate about the actual conditions for the deployment of CRAS as an innovative and essential proposal to the success of SUAS, which represents a breakthrough for social care policy